Prevalence and determinants of periodic limb movements in the general population. Issue 3 (12th February 2016) - Haba‐Rubio, José; Marti‐Soler, Helena; Marques‐Vidal, Pedro; Tobback, Nadia; Andries, Daniela; Preisig, Martin; Waeber, Gérard; Vollenweider, Peter; Kutalik, Zoltán; Tafti, Mehdi; Heinzer, Raphaël
Abstract : Objective: Periodic limb movements during sleep (PLMS) are sleep phenomena characterized by periodic episodes of repetitive stereotyped limb movements. The aim of this study was to describe the prevalence and determinants of PLMS in a middle to older aged general population. Methods: Data from 2, 162 subjects (51.2% women, mean age = 58.4 ± 11.1 years) participating in a population‐based study (HypnoLaus, Lausanne, Switzerland) were collected. Assessments included laboratory tests, sociodemographic data, personal and treatment history, and full polysomnography at home. PLMS index (PLMSI) was determined, and PLMSI > 15/h was considered as significant. Results: Prevalence of PLMSI > 15/h was 28.6% (31.3% in men, 26% in women). Compared to subjects with PLMSI ≤ 15/h, subjects with PLMSI > 15/h were older ( p < 0.001), were predominantly males ( p = 0.007), had a higher proportion of restless legs syndrome (RLS; p < 0.001), had a higher body mass index ( p = 0.001), and had a lower mean glomerular filtration rate ( p < 0.001). Subjects with PLMSI > 15/h also had a higher prevalence of diabetes, hypertension, and beta‐blocker or hypnotic treatments. The prevalence of antidepressant use was higher, but not statistically significant ( p = 0.07). Single nucleotide polymorphisms (SNPs) within BTBD9 (rs3923809), TOX3 (rs3104788), and MEIS1 (rs2300478) genes were significantly associated with PLSMI > 15/h. Conversely, mean hemoglobin and ferritin levels were similar in both groups. In the multivariate analysis, age, male gender, antidepressant intake, RLS, and rs3923809, rs3104788, and rs2300478 SNPs were independently associated with PLMSI > 15/h. Interpretation: PLMS are highly prevalent in our middle‐aged European population. Age, male gender, RLS, antidepressant treatment, and specific BTBD9, TOX3, and MEIS1 SNP distribution are independent predictors of PLMSI > 15/h. ANN NEUROL 2016;79:464–474